Diagnosis and therapy of resistant hypertension in clinical practice - Widecka, Krystyna (Przewodnik Lekarza/Guide for GPs, 2011)
Resistant hypertension is a common clinical problem faced by both primary-care and specialists. Cardiovascular risk is undoubtedly increased in patients with resistant hypertension. Current guidelines give recommendations concerning management of patients with resistant hypertension. It is also the subject of a separate scientific statement of the American Heart Association. The article discusses selected aspects of management of patients with resistant hypertension.